POLLEN MORPHOLOGY OF CERTAIN TROPICAL PLANTS - A. N. RAO, LEONG FONG LING (Reinwardtia, 1974)
The pollen morphology of 49 species belonging to 48 genera and 31 families ia recorded in this paper. Of these 24 and 19 taxa are studied at generic and species level respectively.Six species are redescribed to show the variations in the local pollen grains. In most of the species studied presently the characters were similar to those recorded previously for the respective families.The variations seen in some of the taxa with regard to wall characters,nature of the apertures,etc. are poninted out.The present observations ace comparatively discussed with reference to previous literature